2017
DOI: 10.1097/bsd.0000000000000305
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral End-Plate Perforation for Intervertebral Disc Height Preservation After Single-level Lumbar Discectomy

Abstract: The present study showed positive correlation between the volume of removed disc tissue and decrease in postoperative ISV and ISH. There were no statistically significant differences in ISV and ISH between the group with end-plate perforation and the control group 6 months after lumbar discectomy. Clinical outcome and disability were significantly improved in both groups 3 and 6 months after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 26 publications
0
9
0
Order By: Relevance
“…Parker et al also reported that 32% of patients suffered back pain after conventional discectomy, and 9% of cases underwent fusion surgery for pain control [ 20 ]. Vodicar et al reported that invasive procedures, including endplate perforation, decrease vertebral height and worsen back pain in the postoperative period [ 21 ]. Scarring of the epidural space can be problematic [ 22 – 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parker et al also reported that 32% of patients suffered back pain after conventional discectomy, and 9% of cases underwent fusion surgery for pain control [ 20 ]. Vodicar et al reported that invasive procedures, including endplate perforation, decrease vertebral height and worsen back pain in the postoperative period [ 21 ]. Scarring of the epidural space can be problematic [ 22 – 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Parker et al also reported that 32% of patients suffered back pain after conventional discectomy, and 9% of cases underwent fusion surgery for pain control [12]. Vodicar et al reported that invasive procedures, including endplate perforation, decrease vertebral height and worsen back pain in the postoperative period [13].…”
Section: Discussionmentioning
confidence: 99%
“…1). Eighteen studies met the selection criteria for the purposes of the present review, which included two RCTs [27,28] and 16 observational studies [12,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43].…”
Section: Study Selectionmentioning
confidence: 99%
“…DH method-1b on L1/2-L5S1: average of anterior, middle, and posterior DH = (a + b + c)/3) to measure the DH [28,29,31,32,36,[41][42][43].…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation